2005
DOI: 10.1074/jbc.m413948200
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and Pharmacologic Factors Influencing GlyceroneogenicContribution to Triacylglyceride Glycerol Measured by Mass IsotopomerDistribution Analysis

Abstract: An imbalance between triacylglycerol synthesis and breakdown is necessary for the development of obesity. The direct precursor for triacylglycerol biosynthesis is ␣-glycerol phosphate, which can have glycolytic and glyceroneogenic origins. We present a technique for determining the relative glyceroneogenic contribution to triacylglyceride glycerol by labeling the glycerol moiety with 2 H 2 O. The number of hydrogen atoms (n) incorporated from H 2 O into C-H bonds reflects the metabolic source of ␣-glycerol pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
68
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 38 publications
(51 reference statements)
1
68
1
Order By: Relevance
“…Fasting glycerol output from WAT was not decreased during a rosiglitazone treatment as would be expected if Gyk activity was upregulated (31). Moreover, elegant in vivo experiments using heavy water showed that, under rosiglitazone treatment, GyK is unlikely to contribute to triglyceride synthesis in adipose tissue (33). The lack of induction in human fat cells is probably related to the absence of PGC-1␣ upregulation because this mechanism has been proposed as essential for the induction of GyK by rosiglitazone in 3T3-L1 adipocytes (20).…”
Section: Discussionmentioning
confidence: 71%
“…Fasting glycerol output from WAT was not decreased during a rosiglitazone treatment as would be expected if Gyk activity was upregulated (31). Moreover, elegant in vivo experiments using heavy water showed that, under rosiglitazone treatment, GyK is unlikely to contribute to triglyceride synthesis in adipose tissue (33). The lack of induction in human fat cells is probably related to the absence of PGC-1␣ upregulation because this mechanism has been proposed as essential for the induction of GyK by rosiglitazone in 3T3-L1 adipocytes (20).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, we observed a vigorous remodeling of the fatty acid distribution profile (6). Using 2 H 2 O, Hellerstein and colleagues (7,8) have demonstrated that rates of triglyceride turnover in adipose tissue are depot-specific and sensitive to pharmacological therapy.…”
mentioning
confidence: 90%
“…Although it is clear that the liver can utilize all of these pathways depending on the nutritional/hormonal status, there is an uncertainty regarding the contribution of the various pathways to the formation of ␣-glycerol-3-phosphate in white adipose tissue in vivo. Although many investigators agree that glucose plays an important role in triglyceride synthesis in adipose tissue and that glycerol makes a minor (if any) contribution to ␣-glycerol-3-phosphate (because there is low glycerol kinase activity), the potential for converting pyruvate to ␣-glycerol-3-phosphate (referred to as glyceroneogenesis) is intriguing (7,9,12). For example, investigators have suggested that there should be a glyceroneogenic flux to facilitate fatty acid (re)esterification (13), and that hypothesis is supported by experiments in which ϳ90% of triglyceride glycerol was apparently derived from glyceroneogenesis (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that glyceroneogenesis was the main contributor pathway for fatty acid reesterification in rat adipose tissue in both basal and thiazolidinedione-stimulated conditions [19]. This result was reinforced by elegant in vivo experiments from Chen et al [34], in which mass isotopomer analyses in mice confirmed the major contribution of glyceroneogenesis to thiazolidinedione-induced triacylglycerol synthesis, with a very minor role of glycerol phosphorylation. One important observation of our present work is that the administration of rosiglitazone to insulin-resistant rats induced an increase in glyceroneogenesis, which was accompanied by an improvement in dyslipidaemia, as shown by the large decrease in plasma triacylglycerol.…”
Section: Discussionmentioning
confidence: 71%